METTL3-Mediated ADAMTS9 Suppression Facilitates Angiogenesis and Carcinogenesis in Gastric Cancer - Wang, Nuofan; Huo, Xinying; Zhang, Baoguo; Chen, Xiaoxiang; Zhao, Shuli; Shi, Xuesong; Xu, Hao; Wei, Xiaowei (Frontiers in Oncology, 2022)
Purpose: The role of Methyltransferase-like 3 (METTL3), which participates in catalyzing N-methyladenosine (m6A) RNA modification, is elusive in gastric cancer (GC). Materials and Methods: METTL3 expression in GC was evaluated in clinical samples and transcriptome data profiles gathered from the Cancer Genome Atlas (TCGA). The angiogenic and cancerigenic functions of METTL3 in GC were investigated in vitro and in vivo. The internal control mechanisms of METTL3 were explored by omics and biology experiments. Results: METTL3 was overexpressed in human GC. Functionally, we verified that METTL3 promoted tumor cell proliferation and angiogenesis through a series of phenotypic experiments. Subsequently, ADAMTS9 was identified as the downstream effector of METTL3 in GC which could be degraded by YTHDF2-dependent pathway. Finally, the data suggested that METTL3 might facilitate GC progression through ADAMTS9-mediated PI3K/AKT pathway. Conclusions: Our study unveiled the fundamental mechanisms of METTL3 on GC progression.The clinical value of METTL3 in GC deserves further exploration.